2006
DOI: 10.1051/0004-6361:20054138
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic H2O masers and X-ray absorbing column densities

Abstract: Having conducted a search for the λ ∼ 1.3 cm (22 GHz) water vapor line towards galaxies with nuclear activity, large nuclear column densities or high infrared luminosities, we present H 2 O spectra for NGC 2273, UGC 5101, and NGC 3393 with isotropic luminosities of 7, 1500, and 400 L . The H 2 O maser in UGC 5101 is by far the most luminous yet found in an ultraluminous infrared galaxy. NGC 3393 reveals the classic spectrum of a "disk maser", represented by three distinct groups of Doppler components. As in al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 126 publications
4
103
0
1
Order By: Relevance
“…The value for the nuclear column densities is a continuous function that spans a range of values between 10 21.08 cm −2 (M 82) and 10 24.75 cm −2 (M 51; although the values for NGC 6300 and NGC 2273 are only lower limits). Indeed, as qualitatively suggested by Zhang et al (2006), the kilomasers associated, or most likely associated, with AGN activity are found in galaxies with higher nuclear column densities (10 23 cm −2 < N H < 10 25 cm −2 ), different from those with a star-forming origin, which are found in galaxies with nuclear column densities <10 23 cm −2 . The only exception is represented by the maser in NGC 253 that, despite being quite confidently associated with star formation (Hofner et al 2006;Brunthaler et al 2009), Histogram showing the number of H 2 O kilomaser galaxies as a function of their nuclear column density derived from X-ray spectroscopy.…”
Section: Kilomasers Revisitedmentioning
confidence: 58%
See 3 more Smart Citations
“…The value for the nuclear column densities is a continuous function that spans a range of values between 10 21.08 cm −2 (M 82) and 10 24.75 cm −2 (M 51; although the values for NGC 6300 and NGC 2273 are only lower limits). Indeed, as qualitatively suggested by Zhang et al (2006), the kilomasers associated, or most likely associated, with AGN activity are found in galaxies with higher nuclear column densities (10 23 cm −2 < N H < 10 25 cm −2 ), different from those with a star-forming origin, which are found in galaxies with nuclear column densities <10 23 cm −2 . The only exception is represented by the maser in NGC 253 that, despite being quite confidently associated with star formation (Hofner et al 2006;Brunthaler et al 2009), Histogram showing the number of H 2 O kilomaser galaxies as a function of their nuclear column density derived from X-ray spectroscopy.…”
Section: Kilomasers Revisitedmentioning
confidence: 58%
“…N H > 10 24 cm −2 . In particular, Zhang et al (2006) found that, for kilomasers, two groups were apparently present, one with nuclear column densities of 10 21−22 cm −2 and another with nuclear column densities of >10 23.3 cm −2 . Furthermore, it was put forward that the few nuclear kilomasers have an average column density that is indistinguishable from those of the entire megamaser sample.…”
Section: Kilomasers Revisitedmentioning
confidence: 97%
See 2 more Smart Citations
“…The observing sample is considered towards the extended X-ray galaxies which show megamaser emission from water or OH, since the detection rate of class I methanol masers should tend to be higher in sources with megamasers. The target sample for our survey includes eight water megamaser galaxies (among them two galaxies which also host OH megamasers) which also exhibit soft X-ray emission detected in Chandra and/or XMM-Newton observations (Zhang et al 2006;Brassington, Ponman & Read 2007). In addition, we also include eight OH megamaser galaxies with extended X-ray emission detected in ROSAT observations (Kandalyan 2003).…”
Section: S O U R C E S a M P L E A N D O B S E Rvat I O Nmentioning
confidence: 99%